Socialist Women and the Great War, 1914-21 : Protest, Revolution and Commemoration - Painter, Corinne HerausgeberIn; Sharp, Ingrid HerausgeberIn; Stibbe, Matthew 1969- HerausgeberIn (Bloomsbury Academic, 2022)
Socialist Women and the Great War: Protest, Revolution and Commemoration, an open access book, is the first transnational study of left-wing women and socialist revolution during the First World War and its aftermath. Through a discussion of the key themes related to women and revolution, such as anti-militarism and violence, democracy and citizenship, and experience and life-writing, this book sheds new and necessary light on the everyday lives of socialist women in the early 20th century. The participants of the 1918-1919 revolutions in Europe, and the accompanying outbreaks of social unrest elsewhere in the world, have typically been portrayed as war-weary soldiers and suited committee delegates—in other words, as men. Exceptions like Rosa Luxemburg exist, but ordinary women are often cast as passive recipients of the vote. This is not true; rather, women were pivotal actors in the making, imagining, and remembering of the social and political upheavals of this time. From wartime strikes, to revolutionary violence, to issues of suffrage, this book reveals how women constructed their own revolutionary selves in order to bring about lasting social change and provides a fresh comparative approach to women's socialist activism. As such, this is a vitally important resource for all postgraduates and advanced undergraduates interested in gender studies, international relations, and the history and legacy of World War I. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollection.com. Open access was funded by Knowledge Unlatched